Analisis Faktor – Faktor yang Mempengaruhi Tingkat Pendapatan Pemilik Usaha Industri Kecil-Menengah (Studi Kasus Industri Kecil-Menengah Makanan Ringan di Desa Talok Kecamatan Turen Kabupaten Malang) - Unda ikmana Dean Prisatya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the effect of financial capital, the amount of labor, and business experience on income level of small and medim industrial owners with case study on small and medium snacks industrial in Talok village. This research quantitative data used are primary data. Method of regression analysis using doubled regression and transformed into log-linier regression. Research results showed that simultaneous financial capital, the amount of labor, and business experience has a significant effect on the variable income level. In partial income level significantly affected by financial capital(+), the amount of labor(+), and business experience(+) on income level of small and medim snacks industrial in Talok village. The rate coefficient of determination ( ) for the variables that affect working income level amounted to 95.8%, which means the independent variables in the model is able to explain the dependent variable (income level) at 95.8%, the remaining 4.2% is explained by variables outside this model.Keywords : Income Level, Financial Capital, Labor, Business Experience